Insider ownership and default risk: What does the data reveal about Japanese firms? - Humaira Haque; Md. Nurul Kabir; Syeda Humayra Abedin; Mohammad Dulal Miah; Parmendra Sharma (China Accounting and Finance Review, 2024)
The ownership structure in Japanese firms has experienced a significant change recently, fueled primarily by regulatory changes. This has important repercussions on corporate performance and risk. This paper examines the impact of insider ownership on the default risk of Japanese firms. We collected data from the Nikkei Corporate Governance Evaluation System (CGES) database for the period 2004–2019. Our final dataset yields 36,116 firm-year observations. We apply a firm fixed effect model for baseline regression. Endogeneity was checked by applying propensity score matching (PSM) and two-stage least squares (2SLS) techniques. Furthermore, the robustness of baseline regression results was checked using alternative estimation techniques. Results show a significant positive influence of insider ownership on default risk. Furthermore, ROA volatility and stock price volatility appear to be the major channels through which insider ownership affects a firm’s default risk. We further document that external monitoring mechanisms, including traditional main bank ties, institutional ownership and analyst coverage, are the key risk-mitigating factors. Our research deals with Japanese firms only. Future research may attempt to analyze the cases of emerging economies. Furthermore, future research might examine the ownership-default risk relationship for financial institutions to see if this relationship differs between financial and nonfinancial firms. Insider ownership enhances the probability of default. Hence, policymakers may consider instituting a ceiling for insider ownership in Japanese firms. Moreover, we highlight various risk-mediating channels that would help policymakers adopt guidelines for mitigating corporate risk. Our study is the first to investigate the effect of insider ownership on default risk in Japanese settings. Prior studies identified various determinants that affect firms’ default risk. Our study contributes to this stream of literature by examining the impact of insider ownership on default risk and extending the limited literature related to insider ownership.